Molecular characterization of insecticide resistance in larval population of Spodoptera litura (Fab.): MOLECULAR CHARACTERIZATION OF INSECTICIDE RESISTANCE IN SPODOPTERA LITURA - E CHANDRAYUDU; T MURALI KRISHNA; K VEMANA (Journal of Oilseeds Research, 2017)
Acetylcholinesterase gene activity in populations of Spodoptera litura (Fab.) collected from groundnut fields of different regions of Andhra Pradesh and Telangana was compared using a- and b-napthyl acetate as substrate for enzyme reaction. Among insecticide pre exposed S. litura population analyzed, nine out of ten populations showed elevated activities of acetylcholinesterase gene. A specific amplification product at 600 bp region indicating the presence of acetylcholinesterase gene in resistant strains of S. litura, whereas in susceptible base line strain of S. litura it was not found due to non amplification ofspecific gene at the same loci (600 bp) a phenomenon due to low copy number of gene. RAPD-PCR analysis of resistant and susceptible S. litura population revealed the existence of polymorphism. Specific amplification for acetylcholinesterase gene using custom made primers produced amplified product in resistant S. litura populations.